Occupational voice : care and cure - Dejonckere, P. H. (Philippe H.) (Kugler Publications ; Distributor for USA and Canada, Library Research Associates, 2001)
""People using their voice professionally are at risk for occupational voice diseases, and require specific prevention and treatment"" was the topic focused on by the third Pan European Voice Conference, organized in August 1999 at Utrecht University. The present book includes the main tutorial lectures, with reviews of the most relevant research data and opinions regarding this specific area of concern. Occupational voice users include not only singers and actors, but also teachers, politicians, lawyers, clergymen, telephone operators, etc.(1). The pathogenesis of voice disorders in such patients can be primarily related to their occupation, and thus, after adequate differential diagnosis, these need to be recognized as true occupational diseases, in the same way as, for example, occupational hearing loss"--Introduction, page [vii]